Optimization of Electromangnetic Band Gap Structure for Mutual Coupling Reduction in Antenna Arrays-A Comparative Study - Praveen Kumar, K; Khan, Habibullah (International Journal of Engineering and Technology, 2018)
In this paper, two new three layer (stacked) Electromagnetic Band Gap structures are proposed, named as Stacked Electromagnetic Band Gap (SEBG) and Progressive Stack Electromagnetic Band Gap (PSEBG) structures. Its electromagnetic (EM) properties are determined by using Finite element method (FEM) based simulator and obtained results are compared with classical mushroom type electromagnetic band gap (MEBG) structure. Both SEBG and PSEBG structures proposed in this paper consists of two layers above the conducting ground plane; a lower layer, contains array of small MEBGs with square patches and an upper layer contains square planar MEBG structure. Vertical conducting stubs passing through substrate shorting all square patches in both the layers with conducting ground. Three EBG structures are exhibiting the property of forbidden band gap (FBG), where surface wave propagation is restricted. The FBG property helps in minimization of mutual coupling between array antennas when electromagnetic band gap structures are incorporated between array elements. In this paper, the level of coefficient of mutual coupling between array antenna in the presence of SEBG and PSEBG are investigated, obtained results are compared with classical MEBG results. The co-efficient of mutual coupling is reduced up to 12dB in the presence of proposed models.